A priori skepticism, conventionalism and contextualism - Salem, Sherif Mohamed Gamal (AUC Knowledge Fountain, 2016)
In this thesis we propose a skeptical scenario about a priori knowledge. The scenario is composed of three main arguments: the a priori brain-in-a-vat argument, the problem of deduction, and the rule–following paradox. We propose a solution for a priori skepticism that is based on two philosophical schools: conventionalism and contextualism. Finally, we provide a sufficient condition – although hard to satisfy – for relieving a priori skepticism.